Qualidade de vida no trabalho: subsídios para um plano de melhoria em função da percepção dos servidores ativos da UFSM - Parcianello, José Adroaldo (2015)
This study aims to analyze the perception of the active UFSM servers in relation to QVT through the actions developed by the Coordination of Health and Quality of Life Server - CQVS. It has been observed that over the years the Institution is investing in QVT for it servers, therefore demanding an extensive review of these actions from the point of view of the servers. Within this context, this study presents a quantitative and qualitative descriptive approach to the problem. As technical procedure is based on the study of case of the study unit Federal University of Santa Maria, a Federal Education Institution multicampus, located in the cities of Santa Maria (campus office), Frederico Westphalen, Palmeira das Missões, Silveira Martins and most recently Cachoeira do Sul, reaching a population of teachers and Technical Administrative servers in Education - TAE 4,686 servers. Data collection was through document analysis, participant observation and questionnaire consisting of three parts: the first for the socio-demographic profile of respondents, followed by closed questions according to the QVT model Walton (1973) and the third part with specific issues related to actions undertaken by CQVS. The processing and analysis of data were first reviewed and coded numerically and introduced in Windows Excel software and later analyzed with the help of Statistical Package for Social Sciences - SPSS. Also statistics and frequency analysis related to variables surveyed were held. With the results an action plan was proposed containing activities related to quality of working life in order to contribute to the improvement of activities in compliance with the demands of servers. It stands out in this plan a periodic disclosure on CQVS and dissemination of their actions in the UFSM and Progep sites, create a visitation committee at UFSM, conduct periodic QVT surveys in the institution and create manual regarding the duties and offered services to servers by the Coordination, among other actions presented in this study.